ASAS INDEMNITAS DAN KAFÂLAH DALAM ASURANSI SYARIAH - Saharuddin, Desmadi (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
The main objectives of a person to invest are to become wealthier and to gain tranquility in his life. It becomes absurd when the right customers for indemnity (kafâlah) towards customers who received a risk become unguaranteed. The customer is often difficult to understand the terms contained in the insurance policy that written in a very small font. The ambiguities of these terms become significant obstacles in the settlement of claims. Cases of claim are mostly the result of the customer’s difficulty in understanding these terms and the lack of a good explanation of the company concerning the content of the policy.DOI: 10.15408/aiq.v5i1.2560